ON GROWTH RESPON AND RESULTS OF UPLAND RICE DUE TO THE ALLOTMENT OF SOME A DOSE OF COMPOST BAMBOO LEAVES - M.Si, Dr.Yusnaweti (Menara Ilmu, 2016)
The research “ On Growth Response and the Results of Upland Rice due to the Allotment of Some a Dose of Compost Bamboo Leaves “. On the field and laboratory of Agriculture Faculty, Muhammadiyah University of West Sumatera. Research purposes , to get a dose of compost bamboo leaves which is proper for upland rice . This is a experiment in Completely Random Blok Design,, with 5 level and 3 replication of dose of compost bamboo leaves 0 , 5 , 10 , 15 and 20 t / ha. Data observation dianalis in statistika by test f the first real 5 percent. The results showed research for growth and uplang rice the results of a dose 20 t / ha give the best results for growth and the results of upland rice . Key words : Compost bamboo leaves ; upland rice